ONLINE LEARNING IN THE PANDEMIC COVID -19: PERCEPTIONS OF PHYSICAL EDUCATION STUDENTS - Didik Cahyono (Jurnal Education and Development, 2021)
The Covid-19 pandemic has changed the way people live, including in the field of education. To avoid increasing cases, the Minister of Education, Culture, Research, and Technology has made a policy regarding the online teaching and learning process. This study aims to determine student perceptions of online learning during the Covid-19 pandemic. This study uses a quantitative descriptive analysis method with the research instrument in the form of a questionnaire distributed online with the help of Google Forms. The number of samples in this study was 115 students of the Physical Education Study Program who had been involved in online learning during the Covid-19 pandemic. The results showed that 100% of students of the Physical Education Study Program, Faculty of Teacher Training and Education, Mulawarman University carried out online learning in the even semester of the 2020/2021 academic year. The online media that students are most interested in when learning online are MOLS (Mulawarman Online System) 81.7%, Google Classroom (24.4%), Google Hangout (0.9%), Webex, Youtube (15.7%), Whatsapp (59.1%), and Zoom (89.6%). Even so, the majority of students prefer offline learning in face-to-face classes compared to online learning because the subjects in the physical education study program are more practical than the theory